Rural Mothers' Evaluation of the Strong and Weak Points of Child Care - Alice M. Atkinson (Journal of Research in Rural Education, 1996)
Most ofthe 199 rural Midwestern mothers with young children interviewedfor this study rated their caregivers as "good" or "excellent." Mothers' descriptions ofthe strong and weak points ofchild care differed according to the type of care used. Mothers using relatives emphasized personal relationships with caregivers and the characteristics of the caregiver. Mothers using center-based care frequently commented on the programs and service. The patternsfor family day care were less clear. Mothers' evaluations of child care have significant implications for guiding the support and monitoring of child care services in rural areas.